Egmundella fasciculata Fraser 1940 ... - Calder, Dale R.; Choong, Henry H. C. (Zenodo, 2018)
Egmundella fasciculata Fraser, 1940a Egmundella fasciculata Fraser, 1940a: 577, pl. 32, figs. 4a, b. Syntypes. USNM 43436: USA, North Atlantic Ocean off Martha’s Vineyard, R / V Fish Hawk Sta. 949, 40°03’N, 70°31’W, 23 August 1881, rake dredge, 183 m, several colonies or colony fragments, without gonophores, labelled “ type ”; ethanol. Lectotype, by present designation. USNM 43436: USA, North Atlantic Ocean off Martha’s Vineyard, R / V Fish Hawk Sta. 949, 40°03’N, 70°31’W, 23 August 1881, rake dredge, 183 m, one colony, 2.5 cm high, in fairly good condition, without gonophores, labelled “ type ”; ethanol. Paralectotypes. USNM 1458911: USA, North Atlantic Ocean off Martha’s Vineyard, R / V Fish Hawk Sta. 949, 40°03’N, 70°31’W, 23 August 1881, rake dredge, 183 m, several colonies or colony fragments, up to 2.0 cm high, in from good to poor condition, without gonophores; ethanol. BCPM 976-00289-001: USA, south of Martha's Vineyard, 40°03'N, 70°31'W, 23 August 1881, 183 m, several colony fragments, in poor ... : Published as part of Calder, Dale R. & Choong, Henry H. C., 2018, Names of hydroids (Cnidaria, Hydrozoa) established by Charles McLean Fraser (1872 - 1946), excluding those from Allan Hancock Expeditions, pp. 1-83 in Zootaxa 4487 (1) on page 25, DOI: 10.11646/zootaxa.4487.1.1, http://zenodo.org/record/1456161 ...